2012
DOI: 10.4236/ajps.2012.39148
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Transformation Studies on Avocado Cultivar “Hass” (Persea americana)

Abstract: The use of traditional breeding for improvement of avocado cultivars is time consuming, hence other methods such as genetic transformation by Agrobacterium is indispensable to adopt. The strain GV3850/pBI121gave best transformation outcome compared to five other binary vectors (AGL1/pCGP904; AGL1/pBI121; GV3850/pCGP904; LBA4404/pCG-P904 and LBA4404/pBI121) under different pH and acetosyringone concentrations. The optimal condition for reliable transformation was by using 200 µM acetosyringone and a pH of 5.2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Jourbert et al (2004 found that the transformation efficiency for tobacco leaves was decreased after addition of 250 lM acetosyringone into inoculation and co-cultivation media. A similar finding was reported by Ahmed et al (2012) where the transformation frequency in avocado cells was decreased drastically at 400 lM acetosyringone. Several studies also indicated that acetosyringone is not an essential factor for Agrobacterium-mediated transformation, particularly in barley (Shrawat et al 2007) and rice (Aananthi et al 2010).…”
Section: Resultssupporting
confidence: 85%
“…Jourbert et al (2004 found that the transformation efficiency for tobacco leaves was decreased after addition of 250 lM acetosyringone into inoculation and co-cultivation media. A similar finding was reported by Ahmed et al (2012) where the transformation frequency in avocado cells was decreased drastically at 400 lM acetosyringone. Several studies also indicated that acetosyringone is not an essential factor for Agrobacterium-mediated transformation, particularly in barley (Shrawat et al 2007) and rice (Aananthi et al 2010).…”
Section: Resultssupporting
confidence: 85%
“…Among the three Agrobacterium strains assessed, we observed that the LBA4404 is suitable for transient expression in avocado leaves. In two previous avocado transformation studies comparing different Agrobacterium strains, the LBA4404 strain did not give the best results, though this may be because the tissue they agroinfiltrated were globular somatic embryonic masses (Palomo-Ríos et al 2012), and embryonic shoot axes (Ahmed et al 2012).…”
Section: Discussionmentioning
confidence: 86%
“…Currently the molecular analyses are hindered by the lack of efficient and rapid transformation protocols. In the last two decades there has only been a single report using biolistics for transient transformation of embryogenic callus (Chaparro-Pulido et al 2014), one report using Agrobacterium rhizogenes to produce composite avocado plants (Prabhu et al 2017), and few reports detailing the use of Agrobacterium to generate stable transformants (Cruz-Hernández et al 1998;Raharjo et al 2003Raharjo et al , 2008Palomo-Ríos et al 2011Ahmed et al 2012). These latter reports employed embryogenic masses derived from zygotic embryos, due to their high potential and competence for regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Certain combinations of host genotypes and bacterial strains have been reported to be more efficient in rooting and transformation in other plant systems as well [ 49 ]. In addition, interactions between the genetic background of the Agrobacterium , binary vectors, acetosyringone concentrations and pH have been shown to have an impact on avocado transformation efficiencies [ 12 ]. Highest transformation efficiencies were achieved in A0.74 upon H+ARqua1(+pBINUbiGUSint) infection.…”
Section: Discussionmentioning
confidence: 99%